Unveiling the dynamics of economic growth, carbon emissions, and energy consumption in Indonesia: a wavelet analysis model - Muttaqin, Ecky Imamul; Primambudi, Ganjar; Darsono, Susilo Nur Aji Cokro (Universitas Muhammadiyah Yogyakarta, 2024)
Climate-related economic growth has been a major topic to current economic development issues. This study tries to examine the causal relationship between economic growth, carbon emissions, and energy consumption in Indonesia using annual data from 1978 to 2022. The data is taken from the World Bank and BP-Statistical Review of World Energy. This study employs wavelet analysis to investigate the complex, time-dependent links among economic growth, carbon emissions, and energy consumption in Indonesia, offering insights into their dynamic interactions across several temporal scales. Granger causality is applied to help uncover temporal relationships and their strength, while wavelet coherence reveals frequency-specific associations across different time scales. This includes analysing cross wavelet power and cross wavelet transform. The study provides a set of research findings, economic growth in Indonesia is still supported by carbon emissions and fuel energy consumption. It shows that fossil fuels continue to dominate the economic growth engine. The consumption of coal and oil is still the leading cause of carbon emissions. This study suggests that the government should enforce consistent regulations, promote collaboration among institutions, and engage public awareness to renewable energy sources. Allocating resources to green investments and incentivizing private industry through financial instruments like carbon trading and green bonds. It can stimulate economic growth while preserving the environment. Moreover, emphasizing the long-term benefits will help establish a sustainable framework for the transition to net-zero emissions.